2020 IEEE International Conference on Artificial Intelligence and Virtual Reality (AIVR) 2020
DOI: 10.1109/aivr50618.2020.00030
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the feasibility of mitigating VR-HMD-induced cybersickness using cathodal transcranial direct current stimulation

Abstract: Many head-mounted virtual reality display (VR-HMD) applications that involve moving visual environments (e.g., virtual rollercoaster, car and airplane driving) will trigger cybersickness (CS). Previous research Arshad et al. (2015) has explored the inhibitory effect of cathodal transcranial direct current stimulation (tDCS) on vestibular cortical excitability, applied to traditional motion sickness (MS), however its applicability to CS, as typically experienced in immersive VR, remains unknown. The presented d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Similar to tunnel travel, the movement speed of the rollercoaster was increased by 20% in the second time window if the same FMS score was reported in consecutive 2-min periods. This rollercoaster application has been shown to induce moderate CS symptoms in young adults in our previous study [37].…”
Section: Vr Tasksmentioning
confidence: 66%
See 2 more Smart Citations
“…Similar to tunnel travel, the movement speed of the rollercoaster was increased by 20% in the second time window if the same FMS score was reported in consecutive 2-min periods. This rollercoaster application has been shown to induce moderate CS symptoms in young adults in our previous study [37].…”
Section: Vr Tasksmentioning
confidence: 66%
“…3) The Cognitive Task (post-moderate CS): According to our previous study in which the time of self-reported full recovery from moderate CS symptoms was less than 5 min [37], we hypothesized that the cognitive domain could be back to being the predominant element in the second cognitive task after the end of moderate CS induction and the 7-min relaxation (2-min break plus 5-min eye-closed baseline session). Indeed, this hypothesis can be verified from the self-reported CS ratings (as explained in Results A).…”
Section: Exploring Hvn-based Cs Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, passenger-centric methods involve presenting additional sensory input (e.g., visual input through a virtual reality (VR) headset or a displays placed in the car interior) [5,7,26], or administering neurostimulation to the passenger (e.g. TMS, tES or tDCs [24]). The validation of both has been explored using different experimental setups.…”
Section: Introductionmentioning
confidence: 99%
“…The validation of both has been explored using different experimental setups. From motion platforms [21,24] and simulators [2,14,37] to on road studies using the Wizard of Oz method [1,5,26,36] or AVs [15].…”
Section: Introductionmentioning
confidence: 99%